A participação feminina no movimento estudantil secundarista como espaço de luta política (anos de 1980) - Patrício, Adriana Cristina da Silva (2007)
The history of women has been an important thematic in the field of Historiography in recent years. Many History scholars have discussed thematics related to genre, pointing out their relationship and conflicts. These new thematics are also the result of a series of changing in history that bring out new problems, subjects and approaches. Our aim in this work is to analise the experience of women militants inserted into the student secondarist movement (ME) in Rio Grande do Norte in the years of 1980 s. Discussing the concepts of History and Spaces, we try to analise the political spaces of ME through public and private spaces that make part of the student militant life, pointing out the conflicts faced during their standing into the movement. To a better understanding of the ME political overview, we set a summary to point out the reconstruction of the student entities reorganized after the military governments, as well as we picture a general picture of this women s insertion in history. We use the oral source as the main methodological resource to the development of our work